(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The current study presents the comprehensive review of heat transfer in liquid metals at low Grashof numbers. Heat transfer in liquid metals is extremely efficient because their substantial thermal conductivity enables heat to travel swiftly, even when natural convection is minimal. At low Grashof numbers, buoyant forces are relatively weak in comparison to viscous forces, hence heat transfer in liquid metals is mainly governed by conduction instead of convection, resulting in restricted fluid motion and decreased thermal transport. The most commonly utilized liquid metals in engineering are alkali metals. Sodium, for example, is primarily employed as a coolant in fast reactors and a working fluid in high-temperature heat pipes. Potassium is an excellent working material for space power plants. Eutectic Na-K and Pb-Bi alloys, as well as Hg, Li, and Ga, may be employed in certain instances. A detailed literature review is needed to compare previous studies under various conditions and highlight the influence of controlling factors such as the Grashof number. This review also discusses the practical importance of comprehending low Grashof number heat transfer for innovative cooling technologies in nuclear, space, and solar thermal applications.